Hot climate cereals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
international conference dealing with the technology of growing cereals in hot climates will take place at the Ngaoundere University Centre in Cameroon from January 22-27,1988